Pelatihan peningkatan kemampuan komputer, internet dan aplikasi desa - Jamaluddin Jamaluddin; Muhammad Ghazali; Muhammad Zohri; Wahyu Ramadhan (Universitas Hamzanwadi, 2022)
Operating a computer as a data processor is needed in all fields. One of the fields that must master Information Technology, and Communication (ITC) skills is the field of government, from the central government to the village government. It is crucial to upgrade the capabilities of computers for village officials because, currently, all data is computerized. The purpose of this community service is to help improve the computer/laptop and internet skills of village staff, especially in Perampuan Village, Labuapi District, West Lombok Regency, NTB. The stages in this service are: analyzing service problems; second, preparing service material; third, carrying out service; and fourth, reporting or post-service activities. The results show increased participant ability on computers and the internet. The participants were enthusiastic about the training on making Google Drive, Google Docs, and Google Spreadsheets because this was the first training they had received. Because creating Google Drive, Google Docs, and Google Spreadsheets is necessary for village services, especially in an era when all residents have smartphones, and all data must now be cloud-based. The village head and the training participants hope the Mataram UIN lecturer service team will still be scheduled to carry out a community service program because the village really needs this service. The participants also suggested that they spend more time so that they are more flexible in the teaching and learning process